Peran ajaran tasawuf dalam membentuk kesadaran moral peserta didik di pondok pesantren sabilurrosyad - Romadhoni, Muhammad Fadil; Ma’arif, Alfian Fahmi (Maliki Interdisciplinary Journal, 2026)
Moral consciousness is a key foundation for students’ character development because it shapes how individuals judge right and wrong, anticipate consequences, and take responsibility for their actions. In Islamic boarding schools (pesantren), moral education is not only taught normatively but is also cultivated through spiritual habituation that strengthens self-control and social sensitivity. This article examines the role of tasawuf (Sufism) in shaping students’ moral consciousness at Sabilurrosyad Islamic boarding school. The study employs a qualitative case-study approach using semi-structured interviews with teachers and students, observations of moral-spiritual programs (dhikr, religious lessons, self-reflection), and document analysis. Findings indicate that tasawuf practices embedded in pesantren culture strengthen emotional regulation, self-reflection, and value internalization, which correspond to improved honesty, patience, empathy, and social responsibility. Challenges include ritualistic understandings of tasawuf and diverse levels of students’ spiritual readiness, requiring an inclusive and contextual approach.